Analysis of the economic, financial situation of hospitals - Lucas de Lima Neto (O Mundo da Saúde, 2011)
The organizational health of a hospital is fundamental, so that it can provide population with suitable health services. This paper aimed at contributing to the analysis of the financial management practices in Brazilian hospitals by studying some economic, financial indicators. It is a document and exploratory research based on secondary data: 127 financial statements of 31 hospitals located in the Greater São Paulo region from 2003-2008 period were collected. One found a strong correlation between the current liquidity and the percentage of financial assets over the total assets, a strong to moderate correlation between the current liquidity and the operating margin, and a weak to moderate correlation between the current liquidity and the EBIT margin. It was possible to observe that the good financial performance of the hospitals in the analyzed periods was influenced by huge amounts destined for investments. The decision to invest expressive amounts in these investments instead of operating assets seems to indicate a strategic decision of the hospitals towards making use of the high rates of the financial market in periods when the profitability of the hospital business showed low to negative operating profit margins. This kind of formation of a set of reserve of resources could point out a defensive posture of avoiding investments on the basis of burdensome financings, particularly in times characterized by higher interest rates.